Stars, stripes and scripts: Innovations and challenges in US pharmacy - Roshan Tasgaonkar (Future Healthcare Journal)
Pharmacy practice in the United States has evolved, transitioning from simple dispensing to complex compounding and medication management. Pharmacists play important roles across many sectors, including clinical care, pharmaceutical industry, insurance companies, and public health. Pharmacists optimize therapy, improve patient outcomes, and reduce healthcare costs. However, the profession faces challenges such as burnout, understaffing and declining insurance reimbursements, particularly in independent pharmacies. Pharmacy Benefit Managers (PBMs) have exacerbated these issues, controlling drug prices and reducing pharmacy profitability through opaque pricing and monopolistic practices. Recent legislative efforts in states like New York have aimed to curb PBM influence, however issues persist, and nationwide legislation is lacking. The future of pharmacy depends on addressing these challenges through unified lobbying and proactive reform. Despite these hurdles, scope of practice and innovation within the field continues to grow, offering hope for a revitalized pharmacy landscape.